If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 3 = 2m + 15 Reorder the terms: 3 + 6m = 2m + 15 Reorder the terms: 3 + 6m = 15 + 2m Solving 3 + 6m = 15 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 3 + 6m + -2m = 15 + 2m + -2m Combine like terms: 6m + -2m = 4m 3 + 4m = 15 + 2m + -2m Combine like terms: 2m + -2m = 0 3 + 4m = 15 + 0 3 + 4m = 15 Add '-3' to each side of the equation. 3 + -3 + 4m = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 4m = 15 + -3 4m = 15 + -3 Combine like terms: 15 + -3 = 12 4m = 12 Divide each side by '4'. m = 3 Simplifying m = 3
| x^3+x^2+5=155 | | x^3+x^2+5=156 | | x^3+x^2+5=45 | | 3z/7-5=9 | | z/7-2=10 | | 3z/7-6=-1 | | tan(5x+0.5)=3 | | senx=015 | | 7x-2=-7 | | 64=y/4 | | 7.5x+9.6(23-x)=204 | | 50c^2-98d^2=0 | | 72x^2-17x=0 | | 50d^2-98d^2=0 | | 7.5x+9.6(23-x)=20 | | 10h-13=17 | | 4z/9-8=-7 | | 4+3x+x+6= | | 15+8=63 | | Uw+vw=0 | | 5w-6=1 | | 6m+4=24 | | x^2-11y^2=1 | | (x-6)(x-6)-(x-4)(x-9)=x | | -14+4=5(x+6)-3(3-x) | | x^2-32x+144=0 | | -3x^2+6x+6=0 | | 8x-10=15+3x | | 2.4x+47.2=14.0-14.2x | | m^2+8m= | | 875-120x-4x^2=0 | | 3(2x+3)=4x-15 |